The effect of cylinder liner operating temperature on frictional loss and engine emissions in piston ring conjunction. (1st April 2017) - Rahmani, R.; Rahnejat, H.; Fitzsimons, B.; Dowson, D.
Highlights: Cylinder liner temperature affects frictional losses. Optimum liner temperature improves energy efficiency and reduces emissions. Liner temperature is hardly affected by viscous shear of lubricant. This implies optimum conditions would be independent of engine speed. Abstract: Despite extensive research into alternative methods, the internal combustion engine is expected to remain as the primary source of vehicular propulsion for the foreseeable future. There are still significant opportunities for improving fuel efficiency, thus directly reducing the harmful emissions. Consequently, mitigation of thermal and frictional losses has gradually become a priority. The piston-cylinder system accounts for the major share of all the losses as well as emissions. Therefore, the need for an integrated approach, particularly of a predictive nature is essential. This paper addresses this issue, particularly the role of cylinder liner temperature, which affects both thermal and frictional performance of the piston-cylinder system. The study focuses on the top compression ring whose critical sealing function makes it a major source of frictional power loss and a critical component in guarding against further blow-by of harmful gasses. Such an integrated approach has not hitherto been reported in literature. The study shows that the cylinder liner temperature is critical in mitigating power loss as well as reducing Hydrocarbon (HC) and Nitrogen Oxide (NOx) emissions from the compression ring – cylinder liner conjunction. The results imply the existence of an optimum range for liner working temperature, independent of engine speed (at least in the studied cases) to minimise frictional losses. Combined with the study of NOx and HC emissions, the control of liner temperature can help to mitigate frictional power loss and reduce emissions.